Investigando vieses de gênero a respeito de profissões entre alunos das áreas de ciências exatas e humanas - Moreira, Murilo César (2020)
Gender stereotypes affect both men and women since childhood. While men may be more often associated with Science, Technology, Engineering, and Math (STEM) careers, women tend to associated with careers related to nurturing and caring. The present research aimed to use an explicit scale and an IRAP to investigate how the gender-career relational pattern could vary for Brazilian college students following their gender and career. Both instruments included as stimuli names of stereotypically regarded as "male" or as "female" careers (pedagogy, nursing, fashion, nutrition, and psychology) and words describing gender. Participants were divided into four groups (men and women from humanities and STEM careers). They performed an IRAP task regarding gender and careers and then filled an explicit scale. A significant pro-male-STEM bias emerged for all groups, except the STEMfemale group, which was the only group showing a significant pro-female-STEM bias (p<.05) and a significant difference from the other 3 groups. The significant pro-male-careers regarded as male bias was especially stronger among STEM-male students but also found in male-humanities and female-humanities groups. In the explicit scales, participants showed a tendency to select a more neutral position (i.e., not classifying careers as "male" or "female"), especially among careers commonly viewed as more "masculine". Considering the participants as single group, correlations were found only between explicit evaluations for the careers more often seen as male and the female-careers regarded as male trial-type indicating that the more a career was explicitly evaluated as male, the more the trial type "STEM Female" was considered "false".